2005
DOI: 10.1016/j.mehy.2005.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Insights from a novel tumor model: Indications for a quantitative link between tumor growth and invasion

Abstract: Both the lack of nutrient supply and rising mechanical stress exerted by the microenvironment appear to be able to cause discrepancies between the actual, observed tumor mass and that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 11 publications
1
24
0
Order By: Relevance
“…For instance, one could hypothesize that genetic and epigenetic profiles which increase the tumor's invasive behavior are selected for at a relatively early stage -a process that would have implications both for diagnostics and therapeutics alike. Furthermore, we argue that this surface-expansion due to nourishment requirements complements the cell density-and thus largely mechanically-driven trigger, described in detail in Deisboeck et al (2005).…”
Section: Figure 1 Herementioning
confidence: 60%
“…For instance, one could hypothesize that genetic and epigenetic profiles which increase the tumor's invasive behavior are selected for at a relatively early stage -a process that would have implications both for diagnostics and therapeutics alike. Furthermore, we argue that this surface-expansion due to nourishment requirements complements the cell density-and thus largely mechanically-driven trigger, described in detail in Deisboeck et al (2005).…”
Section: Figure 1 Herementioning
confidence: 60%
“…As an example, cell density modulates focal adhesion kinase (Fak) activation, a regulator of glioma invasion [19,20]. Deisboeck et al, have suggested that the onset of invasion marks the time point when the tumor's cell density reaches a compaction maximum [21]. One difference between cells within invasive tumor cell islets and those in the bulk tumor we sampled with LCMD was relative local tumor cell density.…”
Section: Resultsmentioning
confidence: 99%
“…The microscopic histological images shown in our previous work [27] also indicate the "island" structure and high density of cancerous cell. The higher cell density in cancerous prostate tissue [29,33,34] gives the molecules less "free" rotation space [10,29,34]. In addition, the dye crowds more in cancerous tissue due to higher adsorption levels of bound Cytate as shown by the larger emission intensity in Fig.…”
Section: B Time-resolved Fluorescence Polarization Anisotropy Of Cytmentioning
confidence: 97%
“…First the tumor grows in volume; when it reaches some kind of confining volume, the mechanical pressure increases its cell density. When the tumor cell density exceeds a certain compaction maximum, invasion starts [29,33]. The tumor grading system for prostate cancer includes the well known five Gleason grades, usually denoted as stages 1-5 [34].…”
Section: B Time-resolved Fluorescence Polarization Anisotropy Of Cytmentioning
confidence: 99%